Circulating endothelial cells as a marker of endothelial dysfunction in patients with psoriatic arthritis - Anastasia Bilukha (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2023)
Abstract. Psoriatic arthritis (PsA) is a chronic progressive inflammatory disease that involves damage of the skin and joints and leads to the development of cardiopulmonary diseases. Mortality among this cohort is 1.28 times higher than the population level. The presence of a prolonged systemic inflammatory process is a significant predictor of the development of cardiovascular (CV) diseases due to the progression of endothelial dysfunction (ED). Objective. To evaluate the role of circulating endothelial cell (CEC) levels as a marker of endothelial dysfunction in patients with psoriatic arthritis. Materials and Methods. We examined 97 patients diagnosed with PsA and 25 clinically healthy patients who formed the control group. All patients underwent diagnostic methods characterizing the course of the disease, assessment of endothelium-dependent vasodilation (EDVD) in response to reactive hyperaemia and CEC levels. Results. The results of the study of endothelial function in patients with PsA demonstrated that reduced EDVD (less than 10 %) was more common among patients with PsA compared to the control group (75.3 % vs. 11.8 %, respectively). The analysis of the CEC content in peripheral blood showed a significant difference (7.15 ± 0.19 and 4.05 ± 0.11, respectively, p < 0.001) between patients with PsA and the control group. In addition, were established the relationships between endothelial dysfunction and the state of endothelial vasodilatory function (rs = -0.91, p < 0.05), disease duration (rs = 0.69, p < 0.05), disease activity (DAPSA (rs = 0.65, p < 0.05), inflammatory process itself (ESR (rs = 0.39, p < 0.05), CRP (rs = 0.52, p < 0.05) and skin lesion prevalence (PASI (rs = - 0.42, p < 0.05)). Conclusions. Our studies suggest a significant prevalence of ED in patients with PsA. The high values of negative correlation between EDVD and CEC are quite expected and comparable to modern studies and allow us to consider desquamated endothelial cells as an independent marker for assessing the state of the endothelium in patients with PsA and are consistent with the literature.